Reading stories in Arabic: the impact of lexico-phonological and diglossic distance level on comprehension and receptive and productive vocabulary among Arab kindergarten children - Shahbari-Kassem, Abeer; Asli-Badarneh, Abeer; Hende, Nareman; Roby-Bayaa, Amal (Frontiers in Education, 2024)
Purpose: This study aims to investigate the impact of the lexico-phonological diglossic distance of story reading (a scaffolded storybook intervention, informed by Vygotsky's theory of scaffolding and fading) on Arabic-speaking preschool children's comprehension and receptive and productive vocabulary. Method: The participants were 139 Israeli-Palestinian kindergartners: 71 composed an intervention group and 68 composed a comparison group. The intervention group heard stories gradually from the SpA, identical, cognate, and unique word forms, whereas the comparison group heard traditional stories unrelated to their lexico-phonological distances. Story 1 was read in unique spoken Arabic (SpA) form, stories 2 and 3 were read in 58% and 45% identical and cognate word forms, respectively, and story 4 was read in 70% unique word forms. Results: The results clearly showed that children’s vocabulary and story understanding was significantly higher after the intervention, especially noticeable in stories that contained a higher proportion of Standard Arabic (StA). Interestingly, the stories told entirely in Spoken Arabic (SpA) were the most effective, yielding the highest scores in both comprehension and vocabulary. Stories that mixed different word forms also performed well, though not as strongly as the SpA stories, while those solely in StA were the least effective. Conclusions: The findings of the study suggest that scaffolded storybook intervention may enhance the receptive vocabulary and comprehension skills of children. This study shows that, in the context of diglossia, stories should be read to children systematically and gradually according to the lexical-phonological distance of words in the stories. Keywords: Arabic; stories; diglossia; lexical phonological distance, receptive, productive, listening comprehension, kindergarten children